Demographic determinants of patronage of medicine hawkers by commercial vehicle passengers in Ghana - Nyarko, Joy Ato; Akuoko, Kofi Osei; Dapaah, Jonathan Mensah; Akuoko, Nana Yaa Serwaa; Iyengunmwena, Egwolo Perpetual (Intelektual Pustaka Media Utama, 2025)
Medicine hawking is one of the major public health problems of the global south. This present study examined the demographic determinants of patronage of the services of medicine hawkers among commercial vehicle passengers in Kumasi, Ghana. A cross-sectional study was carried out from February 2022 to March 2022 at major bus terminals in Kumasi. Data were descriptively and inferentially analysed. The survey revealed that 55% of the respondents had bought medicines from medicine hawkers before. There was a significant relationship between having bought from a medicine hawker before and the intention to buy from them again in the future. Also, age, religion and education contributed significantly to patronising the services of medicine hawkers. We recommend that government intensifies its public health education on the implications of seeking health care services from these medicine hawkers.